The Role of Subuh Education in Developing Students' Characteristics of TPQ Muslimin Ikhwanul Mosque - Ginting, Hairul Rabumansyah; Murniyetti, Murniyetti (Darul Yasin Al Sys, 2023)
This study aims to explore and explore the extent to which the dawn education program at the Al-Qur'an Education Park plays a role in fostering the morals of students. The method used in this study was qualitative research with a case study approach. Data were obtained from three informants who were selected and then interviewed and observed in detail. Then the data collected was analyzed then reduced and presented and in the final stage, conclusions were drawn from the research findings. The findings in the study after being analyzed found that there were several stages of roles in fostering the morals of the students, namely: training the discipline of the students, Amanah, and the students' responsibility in carrying out their duties, and instilling religious values in the students. Furthermore, the research findings found that there were methods used in cultivating the morals of students, namely the exemplary method, the habituation method, and the advice method. Then there are the supporting factors, namely bringing in competent teachers, obeying the rules, guarding the teachers, and parental support. And the inhibiting factor is the existence of children who like to disturb their friends and the many agendas from home. Based on these findings, it is hoped that it can become an illustration in fostering children's morals, especially students who have studied religion, and become initial data for further researchers in discussing different contexts and issues in their research.